A dataset of radar-recorded heart sounds and vital signs including synchronised reference sensor signals - Shi, Kilin; Schellenberger, Sven; Will, Christoph; Steigleder, Tobias; Michler, Fabian; Fuchs, Jonas; Weigel, Robert; Ostgathe, Christoph; Koelpin, Alexander (Scientific data, 2020)
Radar systems allow for contactless measurements of vital signs such as heart sounds, the pulse signal, and respiration. This approach is able to tackle crucial disadvantages of state-of-the-art monitoring devices such as the need for permanent wiring and skin contact. Potential applications include the employment in a hospital environment but also in home care or passenger vehicles. This dataset consists of synchronised data which are acquired using a Six-Port-based radar system operating at 24 GHz, a digital stethoscope, an ECG, and a respiration sensor. 11 test subjects were measured in different defined scenarios and at several measurement positions such as at the carotid, the back, and several frontal positions on the thorax. Overall, around 223 minutes of data were acquired at scenarios such as breath-holding, post-exercise measurements, and while speaking. The presented dataset contains reference-labeled ECG signals and can therefore easily be used to either test algorithms for monitoring the heart rate, but also to gain insights about characteristic effects of radar-based vital sign monitoring. Measurement(s) heart function measurement • heart rate • Respiration • heart sounds Technology Type(s) radar system Factor Type(s) sex • age • weight • height • BMI Sample Characteristic - Organism Homo sapiens Machine-accessible metadata file describing the reported data: https://doi.org/10.6084/m9.figshare.11778900